2017
DOI: 10.11648/j.eco.20170601.11
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Human Resource Accounting on Profitability of Corporate Organization

Abstract: Abstract:This study is to determine the adoption of Human Resource Accounting (increase in staff salary, increment in staff and staff retirement benefits) on the Profitability of Corporate Organizations. Specifically, the study sought; to determine the extent at which increase in staff salary has affected organizational profitability; to ascertain if the increment in staff has contributed positively on organizational profitability and to evaluate the extent at which staff retirement benefits has effect on orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Alekhya & Lakshmi (2020) suggest that HRA is significantly associated with growth metrics, including revenues and net income. Asika et al (2017) found that wage increments, increases in staff level, and retirement perks positively impact organizational profitability, and recommend that a financial reporting standard for HRA be adopted. In service-oriented organizations, human resources are considered the most valuable asset.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Alekhya & Lakshmi (2020) suggest that HRA is significantly associated with growth metrics, including revenues and net income. Asika et al (2017) found that wage increments, increases in staff level, and retirement perks positively impact organizational profitability, and recommend that a financial reporting standard for HRA be adopted. In service-oriented organizations, human resources are considered the most valuable asset.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Profitability is a measure of how much money a business makes after paying all its costs and it shows if a business is successful in generating earnings compared to its expenses (Asika, Chitom & Chelichi, 2017). High profitability means a business is doing well financially and it is important for long-term survival and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Goh (2019) reported that intellectual capacity has tight relationship with corporate performance as well as organizational productivity all respects. Asika, Chitom, and Chelichi (2017) noted that growing importance of human resource accounting cannot be displaced in many years to come in spite the new technologies. Notwithstanding the significance of human resource accounting, human resource accounting over the years has suffered neglect and due recognition in the class of other intangible assets due to some inherent challenges (Fatma, Arzu, & Esen, 2020).…”
Section: Introductionmentioning
confidence: 99%